Research on product color design decision driven by brand image - Zhang, Xinxin; Yang, Minggang; Su, Jianning; Yang, Wenjin; Qiu, Kai (Color research and application, 2020)
As one of the most important visual characteristics in a product system, color can arouse the user's emotional demands quickly. Due to the complexity of the user's emotional needs mining process, it can be expressed by color image adjectives. Meanwhile, product color trends that meet the user's emotional demands may help decision makers to anticipate a new market positioning and reduce the blindness in the product color design. In this study, the Gray theory combined with the Kansei engineering was used to mine the macro and microscopic factors in product color design decision process based on the product color brand image. The results showed that the constructed method could be used to guide the product color design that was to meet the user's emotional needs comprehensively and quickly. The method solved the problems that exist in the current product color trend prediction research and improved the accuracy of the correlation mining between product color design elements and brand image. Lastly, the color design of the mid‐range sedan was taken as an example to prove the feasibility of the research approach. This is a new attempt to guide product color design decisions in two aspects, one is known from the results of product color trends quantitative prediction, and the other one comes from the correlation calculation between product color design elements and brand image.